2011
DOI: 10.1080/15320383.2011.594113
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Phytotoxicity to Radish (Raphanus sativus L.) in a Digested Sludge-amended Gangetic Alluvium

Abstract: A limiting factor in land application of sewage sludge is the resultant heavy metal accumulation in soils followed by biomagnification in the food chain, posing a potential hazard to animal and human health. In view of this fact, pot experiments were conducted to evaluate the effect of digested sludge application to soil on phytotoxicity of heavy metals such as Cd, Cr, Ni, and Pb to radish (Raphanus sativus L.) plants. Increasing sludge levels resulted in increased levels of DTPA-extractable heavy metals in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…In this research, MSC promoted the potato uptake of heavy metals, which is similar to the results of Bozkurt et al (2010) and Bhat et al (2011). This might be attributed to the increased labile fraction proportion of heavy metals.…”
Section: Effects Of Msc On Plant Absorption Of Heavy Metalssupporting
confidence: 92%
See 1 more Smart Citation
“…In this research, MSC promoted the potato uptake of heavy metals, which is similar to the results of Bozkurt et al (2010) and Bhat et al (2011). This might be attributed to the increased labile fraction proportion of heavy metals.…”
Section: Effects Of Msc On Plant Absorption Of Heavy Metalssupporting
confidence: 92%
“…Chelating agents and dilute acids are usually used to assess the potential toxicity of heavy metals, and the heavy metals extracted by chelating agents and dilute acids could represent the long-term available metals in soils (McLaughlin et al, 2000a). The labile fraction proportion of heavy metals increased with increasing MSC percentage in amended sierozem soils (Bhat et al, 2011;Delgado et al, 2012;Arvas et al, 2013). Zubillaga et al (2012) reported that the labile fraction proportion of heavy metals in soil-sludge mixtures decreased with increasing soil OM content.…”
Section: Influence Of Msc On Mobility Of Heavy Metalsmentioning
confidence: 99%
“…5 and 6). Similar results reported for Cr in radish by Bhat et al [2011]. The distribution of metals in different plant tissues depends on their form, water transport and plant species [Ouzounidou et al 1995] therefore, it is difficult to export a general conclusion.…”
Section: Resultssupporting
confidence: 73%
“…In this study, biomonitoring using radishes and PVI index were proposed. Previous research has shown that radishes has exhibited significant responses to changes in contamination levels associated with potential toxic elements and other pollutants in complex matrices (Tiwari et al, 2013;Acosta-Luque et al, 2023;López et al, 2023;Serrano et al, 2023;Bhat et al, 2011).…”
Section: Pollution Riskmentioning
confidence: 99%